Evaluation of the effectiveness of amendments derived from vermicompost combined with modified shell powder on Cd immobilization in Cd-contaminated soil by multiscale experiments - Wang, Feng; Shen, Xuyang; Wu, YuKe; Wang, YiFan; Zhang, Hangjun; Ding, Ying; Zhu, Weiqin (Ecotoxicology and environmental safety, 2023)
The widespread heavy metal contamination of agricultural soils poses an enormous challenge to food safety. To evaluate the Cd immobilization potential of vermicompost combined with modified shell powder (VMSP) on Cd-contaminated soil, batch adsorption tests and field experiments were conducted. First, the Cd2+ removal characteristics and adsorption mechanisms of vermicompost (V), vermicompost combined with shell powder (VSP), and VMSP in an aqueous solution were investigated by batch tests. Then, 3 kg·m2 V, VSP, and VMSP doses were applied to Cd-contaminated farmland soils as soil amendments to plant green garlic (Allium sativum L.) and investigate their Cd immobilization effects in Cd-contaminated soils. Batch adsorption tests showed that VMSP was most effective for Cd2+ removal, with adsorption rates as high as 85.7–99.79% and desorption rates of approximately 1.25–1.34%. Combining further characterization analysis of VMSP, it was demonstrated that the adsorption mechanism of Cd2+ was monolayer chemisorption, mainly involving the complexation reaction of Cd2+ with organic functional groups and the precipitation reaction of Cd2+ with mineral elements. The field experiment showed that adding V, VSP, and VMSP effectively inhibited the enrichment of Cd in green garlic, and the Cd content was reduced by 42.18%, 46.88%, and 68.75%, respectively. However, only the Cd content of green garlic treated with VMSP was lower than the national standard for food safety in China (Cd≤ 0.2 mg·kg-1). V, VSP, and VMSP additions improved soil fertility and reduced Cd bioavailability in the soil by 15.5%, 18.9%, and 36.3%, respectively. In addition, V, VSP, and VMSP addition increased bacterial diversity and improved bacterial communities and functions in the soil by improving basic soil properties and reducing Cd-related toxicity. The results indicated that VMSP is a promising amendment for Cd immobilization in Cd-contaminated farmland soils. [Display omitted] •The mechanism of Cd2+ removal by VMSP in the aqueous phase has been elucidated.•VMSP reduced the bioavailability of Cd in Cd-contaminated soil by 36.3%.•VMSP reduced the content of Cd in green garlic by 68.75%.•VMSP improved soil microbial community structure and function.•VMSP showed great potential in Cd immobilization in Cd-contaminated soil.